Design and swimming test of myliobatid-inspired robot - Songzi GUO; Jun MA; Zhiyin LI; Jinhua ZHANG (Zhongguo Jianchuan Yanjiu, 2022)
ObjectivesOver millions of years of natural selection, fish have evolved various types of swimming modes with various advantages in efficiency, motility and tranquility, making them ideal biological objects on which autonomous underwater vehicles (AUVs) can be modelled. In order to develop a brand new AUV with lower noise and higher mobility, this paper puts forward a design for a myliobatid-inspired robot actuated by pairs of flexible pectoral fins.MethodsThe manufacturing process and actuating method of the prototype are illustrated in detail. In order to test the maximum speed and mobility of the prototype, a series of swimming tests is carried out.ResultsThe experimental results show that the prototype can complete a variety of maneuvers in water, including rolling, small radius steering and hovering, and its maximum swimming speed can reach 1.9 body lengths per second (about 0.73 m/s).ConclusionsThis paper outlines the preliminary design and swimming test of a myliobatid-inspired robot, giving it reference value as an indicator for the next generation of AUVs.